М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
archakova65
archakova65
03.08.2021 18:17 •  Алгебра

Решите уравнение (2x-3)(4x+6x+9)-8x=2,7x;

👇
Ответ:
stigma70
stigma70
03.08.2021
(2x-3)*(4x+6x+9)-8x=2.7x
(2x-3)*(10x+9)-8x= \frac{27}{10}x
20x^2+18x-30x-27-8x= \frac{27}{10} x
20x^2-20x-27= \frac{27}{10} x
200x^2-200x-270=27x
200x^2-200x-270-27x=0
200x^2-227x-270=0
x= \frac{-(-227)\pm \sqrt{(-227)^2-4*200*(-270)} }{2*200}
x= \frac{227 \pm \sqrt{51529+216000} }{400}
x= \frac{227 \pm \sqrt{267529} }{400}
x= \frac{227+ \sqrt{267529} }{400}
x= \frac{227- \sqrt{267529} }{400}
x_1= \frac{227- \sqrt{267529} }{400}, x_2= \frac{227+ \sqrt{267529} }{400}
4,6(23 оценок)
Открыть все ответы
Ответ:
mishustinat
mishustinat
03.08.2021
1                                       1                                     
-- (cos6x + 4cos3x + 3) -  -- (cos6x - 4cos3x + 3) =  
8                                      8                                   

    1                                                                         1
= ( cos6x + 4cos3x + 3 - cos6x + 4cos3x - 3) = --- 8cos3x = cos3x
    8                                                                          8
 
а сорь, там равно 1/2
Тогда, cos3x = 1/2
3x = +arccos1/2 + 2pk
3x = - arccos1/2 + 2pk

3x = pi/3 + 2pk
x1 = pi/9 + 2pk/3

x2 = -pi/9 + 2pk/3
4,7(60 оценок)
Ответ:
kleyman200404
kleyman200404
03.08.2021
1                                       1                                     
-- (cos6x + 4cos3x + 3) -  -- (cos6x - 4cos3x + 3) =  
8                                      8                                   

    1                                                                         1
= ( cos6x + 4cos3x + 3 - cos6x + 4cos3x - 3) = --- 8cos3x = cos3x
    8                                                                          8
 
а сорь, там равно 1/2
Тогда, cos3x = 1/2
3x = +arccos1/2 + 2pk
3x = - arccos1/2 + 2pk

3x = pi/3 + 2pk
x1 = pi/9 + 2pk/3

x2 = -pi/9 + 2pk/3
4,7(24 оценок)
Это интересно:
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ